About one decision of the quasiclassical kinetic equation - S O, Gladkov; S B, Bogdanova (International Journal of Engineering and Technology, 2018)
It has been proved that the solution of the quasi-classical kinetic equation for Bose and Fermi statistics can be represented in the general form, using the relaxation time approximation. The general solution found for the distribution function  helps calculate any non – equilibrium characteristics of metals, magnets, and dielectrics in any order of the perturbation theory according to the relaxation time .